PENGEMBANGAN MULTIMEDIA INTERAKTIF KLBD PADA MATA PELAJARAN MATEMATIKA MATERI KELILING DAN LUAS BANGUN DATAR DI KELAS IV SDN AREN JAYA 1 BEKASI - Dwi Febryanti; Febrianti Yuli Satriyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The learning of mathematics in flat shapes (Circuits and Areas of Squares and Rectangle) in Elementary Schools is learning that builds and develops logical, rational, systematic and critical thinking skills. Through the concept of flat shapes, students can build meaning from the messages generated in communication in learning activities, such as spoken, written, and (graphic) forms. However, learning mathematics is very difficult for elementary school students to understand, this is due to the abstract concept of mathematics. Based on the research data, it was found that the same problems were found in class IV students at SDN Aren Jaya 1 Bekasi, namely that students had difficulty understanding the material around and area of squares and rectangles. This study aims to provide interactive multimedia for learning mathematics that can help students understand the Perimeter and Area of Squares and Rectangle materials. This study uses the ADDIE research method (Analysis, Design, Development, Implementation and Evaluation). The developed media can be declared feasible and valid based on the results of the average score of the language validator who gets a score of 80%, the media validator 81%, and the material validator 80.84%. The results of students' understanding of the material Circumference and Area of Squares and Rectangle have increased with an average value of 55.9 to 82.5.